2022
DOI: 10.1093/ornithapp/duac023
|View full text |Cite
|
Sign up to set email alerts
|

Habitat edges influence the distribution of nest predators for Seaside Sparrows, but not nest placement or success

Abstract: Nest failure for coastal marsh bird species is primarily caused by predation and nest flooding. As sea level rise makes nest flooding more likely, the threat of nest predation will constrain the potential adaptive responses of marsh nesting species. Thus, understanding the predictors of nest predation is important for the conservation of salt marsh-dwelling bird species, such as the Seaside Sparrow (Ammospiza maritima). Predator activity may be influenced by landscape features (particularly habitat edges), pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…New habitats created by road corridors (see Section III.1.a) can act as ecological traps if animals that breed there experience higher predation or parasitism (Section III.4.a) rates. Road proximity is usually negatively related to bird nest survival in temperate regions (Falk, Nol & Burke, 2011;Yoo & Koper, 2017;Newsome & Hunter, 2022) as edge-associated predators use these new habitats for hunting (Small & Hunter, 1988;Thogmartin, 1999;Dijak & Thompson, 2000;Lahti, 2001;Fraser & Whitehead, 2005;Newmark & Stanley, 2011). By contrast, some studies have found no effect (Huhta, 1995;Bechet, Isenmann & Gaudin, 1998;Mettenbrink, Dreitz & Knopf, 2006;Svobodov a, Š alek & Albrecht, 2007) or a positive effect of road proximity on nest survival (Delgado García, Arévalo & Fern andez-Palacios, 2005;Angkaew et al, 2019;da Silva et al, 2019).…”
Section: (B) Effects On Nest Predationmentioning
confidence: 99%
“…New habitats created by road corridors (see Section III.1.a) can act as ecological traps if animals that breed there experience higher predation or parasitism (Section III.4.a) rates. Road proximity is usually negatively related to bird nest survival in temperate regions (Falk, Nol & Burke, 2011;Yoo & Koper, 2017;Newsome & Hunter, 2022) as edge-associated predators use these new habitats for hunting (Small & Hunter, 1988;Thogmartin, 1999;Dijak & Thompson, 2000;Lahti, 2001;Fraser & Whitehead, 2005;Newmark & Stanley, 2011). By contrast, some studies have found no effect (Huhta, 1995;Bechet, Isenmann & Gaudin, 1998;Mettenbrink, Dreitz & Knopf, 2006;Svobodov a, Š alek & Albrecht, 2007) or a positive effect of road proximity on nest survival (Delgado García, Arévalo & Fern andez-Palacios, 2005;Angkaew et al, 2019;da Silva et al, 2019).…”
Section: (B) Effects On Nest Predationmentioning
confidence: 99%